Students' Perception of the Ethical Business Climate: A Comparison With Leaders in the Community - D'Aquila, Jill M. (Journal of business ethics, 2004)
Although undergraduate students are exposed to ethical issues through class assignments, discussions, and readings, they typically do not have first hand experience with business dilemmas. Student opinions on ethical standards and behavior in American business have received scant attention in the literature. The purpose of the study is to provide additional information to both educators and organizations about the ethical perceptions of students. Furthermore, the study contrasts student responses to business and community leaders' responses obtained in a prior study conducted by Touche Ross (1988). The findings from this study are based on an opinion survey about ethics in American business, completed by 476 liberal arts and business students attending a private, religiously affiliated college in New York State. The data indicate numerous differences in perceptions between students and business and community leaders. Differences were also found when students were classified by school (Arts & Science versus Business) and by gender. Overall, students appear to place a strong value on education. Students are the source of new entrants to the business world and the foundation for ethical structures being built by organizations. The findings from this study should assist both educators and employers in the development of necessary programs to maximize the ethical potential of their constituents.